How does angiotensin AT2 receptor activation help neuronal differentiation and improve neuronal pathological situations? - Guimond, Marie-Odile; Gallo-Payet, Nicole (Frontiers in Endocrinology, 2012)
The AT2 receptor of angiotensin II (Ang II) has long been thought to be limited to few tissues, with the primary effect of counteracting the AT1 receptor. Functional studies in neuronal cells have demonstrated AT2 receptor capability to modulate neuronal excitability, neurite elongation, and neuronal migration, suggesting that it may be an important regulator of brain functions. The observation that the AT2 receptor was expressed in brain areas implicated in learning and memory led to the hypothesis that it may also be implicated in cognitive functions. However, linking signalling pathways to physiological effects has always proven challenging since information relative to its physiological functions has mainly emerged from indirect observations, either from the blockade of the AT1 receptor or through the use of transgenic animals. From a mechanistic standpoint, the main intracellular pathways linked to AT2 receptor stimulation include modulation of phosphorylation by activation of kinases and phosphatases or the production of nitric oxide and cGMP, some of which are associated with the Gi-coupling protein. The receptor can also interact with other receptors, either G-protein-coupled such as bradykinin, or growth factor receptors such as nerve growth factor or platelet-derived growth factor receptors. More recently, new advances have also led to identification of various partner proteins, thus providing new insights into this receptor’s mechanism of action. This review summarizes the recent advances regarding the signalling pathways induced by the AT2 receptor in neuronal cells, and discussed the potential therapeutic relevance of central actions of this enigmatic receptor. In particular, we highlight the possibility that selective AT2 receptor activation by nonpeptide and selective agonists could represent new pharmacological tools that may help to improve impaired cognitive performance in Alzheimer’s disease and other neurological cognitive disorders.